Acousto‐Optic Modulation in Silicon Waveguides Based on Piezoelectric Aluminum Scandium Nitride Film. Issue 6 (21st January 2022) - Huang, Chukun; Shi, Haotian; Yu, Linfeng; Wang, Kang; Cheng, Ming; Huang, Qiang; Jiao, Wenting; Sun, Junqiang
Abstract: Aluminum scandium nitride (AlScN) has attracted extensive attention for its excellent piezoelectric properties in the micro‐electromechanical system applications. In this work, AlScN is demonstrated to be a promising candidate for on‐chip acousto‐optic coupling interactions with outstanding piezoelectric properties as well. Based on piezoelectric Al0.6 Sc0.4 N film deposited on silicon‐on‐insulator platform, the proposed devices exhibit impressive acousto‐optic coupling performances over a short interaction length of 210 µm with surface acoustic waves actuated by interdigital transducers. Meanwhile, the acousto‐optic coupling performances are further improved in a compact spiral waveguide with eight interaction segments, where the measured modulation efficiency is enhanced from −21.5 to −12.5 dB and the radiofrequency (RF) 3‐dB bandwidth is narrowed from 4 to 3.1 MHz at central frequency of 3.044 GHz with RF drive power of 18.6 dBm. The measured modulation efficiency is proportional to the incident RF drive power, depicting a linear increasing trend with a slope of one as the RF power increases up to 24.6 dBm. Such acousto‐optic devices are capable of achieving broadband acousto‐optic modulation and narrow‐band microwave photonic filtering. Besides, the designed device structure provides a prospect in single‐sideband modulation, acousto‐optic frequency shift, and nonreciprocal light propagation. Abstract : Acousto‐optic coupling in silicon waveguides based on piezoelectric Al0.6 Sc0.4 N film deposited on silicon‐on‐insulator platform is demonstrated. With a microwave signal loading on the interdigital transducer, the incident optical probe is scattered to optical sidebands by the actuated surface acoustic wave, exhibiting broadband acousto‐optic modulation and narrow‐band microwave photonic filtering.